2019
DOI: 10.1387/ijdb.180400ma
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the cell cycle in early mammalian embryos and its clinical implications

Abstract: Early embryonic development is characterized by a plethora of very complex and simultaneously operating processes, which are constantly changing cellular morphology and behaviour. After fertilization, blastomeres of the newly created embryo undergo global epigenetic changes and simultaneously initiate transcription from the zygotic genome and differentiation forming separate cell lineages. Some of these mechanisms were extensively studied during the last several decades and valuable insight was gained into how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 127 publications
0
9
0
Order By: Relevance
“…In the field of oocyte cryopreservation, research concerning the improvement of the efficiency of in vitro embryo production should give more attention to the progression of embryo development after oocyte fertilization and the first cellular divisions. In the growing embryo, cellular divisions are complex and well-orchestrated processes ( 50 ). Among the event allowing each division, DNA duplication and cytoskeleton dynamic are fundamental, as well as maternal mRNAs, but unfortunately all of these might be damaged in cryopreserved cells ( 3 ), and we cannot rule out that VOs cryoinjuries are inherited by blastomeres after oocyte cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of oocyte cryopreservation, research concerning the improvement of the efficiency of in vitro embryo production should give more attention to the progression of embryo development after oocyte fertilization and the first cellular divisions. In the growing embryo, cellular divisions are complex and well-orchestrated processes ( 50 ). Among the event allowing each division, DNA duplication and cytoskeleton dynamic are fundamental, as well as maternal mRNAs, but unfortunately all of these might be damaged in cryopreserved cells ( 3 ), and we cannot rule out that VOs cryoinjuries are inherited by blastomeres after oocyte cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome segregation during early development in mammals is highly error prone and aneuploidy abounds in oocytes and early embryos ( Hassold and Hunt, 2001 ; Vázquez-Diez and FitzHarris, 2018 ; Radonova et al, 2019 ; Pauerova et al, 2020 ), underscoring the need to understand how the genome is transmitted from one generation to the next. Cohesin is a genome maintenance protein complex required for successful meiosis and mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome segregation during early development is in mammals highly error prone and frequently results in embryos carrying aneuploid blastomeres (Hassold & Hunt 2001, Vázquez-Diez & FitzHarris 2018, Radonova et al 2019. Numerous reports from IVF clinics showed that the aneuploidy affects more than half of human embryos developing in vitro (Carbone & Chavez 2015), although the reported data are sometimes highly variable due to differences in sample preparation and scoring methods between clinical centers (Treff & Zimmerman 2017, Swain 2019).…”
Section: Introductionmentioning
confidence: 99%